2016
DOI: 10.1093/molbev/msw170
|View full text |Cite
|
Sign up to set email alerts
|

A High-CoverageYersinia pestisGenome from a Sixth-Century Justinianic Plague Victim

Abstract: The Justinianic Plague, which started in the sixth century and lasted to the mid eighth century, is thought to be the first of three historically documented plague pandemics causing massive casualties. Historical accounts and molecular data suggest the bacterium Yersinia pestis as its etiological agent. Here we present a new high-coverage (17.9-fold) Y. pestis genome obtained from a sixth-century skeleton recovered from a southern German burial site close to Munich. The reconstructed genome enabled the detecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 69 publications
1
119
0
5
Order By: Relevance
“…Furthermore, the archaeological context of the multiple burials at both sites is normal—these are not the hasty burials we would expect from a period of mass mortality. And although DNA evidence for plague has so far been reported for only a tiny fraction of the skeletal material at both sites (Feldman et al, ; Harbeck et al, ; Wagner et al, ), the results are extrapolated as evidence for an empire‐wide mass mortality event. Harper is resolute.…”
Section: Plagued By Doubt? the Justinianic Pandemic Under Scrutinymentioning
confidence: 94%
“…Furthermore, the archaeological context of the multiple burials at both sites is normal—these are not the hasty burials we would expect from a period of mass mortality. And although DNA evidence for plague has so far been reported for only a tiny fraction of the skeletal material at both sites (Feldman et al, ; Harbeck et al, ; Wagner et al, ), the results are extrapolated as evidence for an empire‐wide mass mortality event. Harper is resolute.…”
Section: Plagued By Doubt? the Justinianic Pandemic Under Scrutinymentioning
confidence: 94%
“…Pathogen aDNA is thought to be preserved within the remnants of the pulp chamber, likely as part of desiccated blood 8,17 . Consequently, tooth sampling has proved successful in the retrieval of whole genomes or genome wide data (that is, low coverage genomes that have provided limited analytical resolution) from ancient bacteria such as Y. pestis 20,[30][31][32][33][34][35][36][37][38][39] , Borrelia recurrentis 40 and Salmonella enterica 41 ; ancient eukaryotic pathogens such as Plasmodium falciparum 42 ; and ancient viruses such as hepatitis B virus (HBV) 43,44 and human parvovirus B19 (B19V) 45 . Even M. leprae, which commonly manifests in the chronic form, has been retrieved from ancient teeth 27,28 .…”
Section: Zoonotic Transmissionmentioning
confidence: 99%
“…Hence, accurate variant calling is critical for drawing reliable evolutionary inferences, although this process is often a challenge when handling data sets derived from samples with high rates of DNA fragmentation (resulting in ultrashort read data), low endogenous DNA content and high levels of DNA dam age. In these cases, increased accuracy is best achieved through stringent NGS read mapping parameters and through visual inspection of the sequences overlap ping the studied SNPs 35 . In addition, histograms of SNP allele frequencies -used to estimate the frequency of heterozygous calls in haploid organisms 26,52 -can often demonstrate the effects of environmental contamination on ancient microbial data sets 41 .…”
Section: Assessing Within-species Evolutionary Relationshipsmentioning
confidence: 99%
“…To the best of our knowledge, recent investigations focussing on analysing the genome of historical pathogens with PCR-or NGS-based methods were limited to archaeological skeletal material (e.g., [69][70][71][72][73][74][75][76][77]) or non-archaeological preserved soft tissues (e.g., [78][79][80]). The first successful investigation on non-archaeological, macerated bones assembled in the pathological collection was performed by Baron et al [24]; we have now demonstrated yet again that these bone samples are suitable for extracting analysable amounts of both human and pathogenic DNA.…”
Section: Discussionmentioning
confidence: 99%